Origin of Short-Chain Organic Acids in Serpentinite Mud Volcanoes of the Mariana Convergent Margin - Eickenbusch, Philip; Takai, Ken; Sissman, Olivier; Suzuki, Shino; Menzies, Catriona; Sakai, Sanae; Sansjofre, Pierre; Tasumi, Eiji; Bernasconi, Stefano M.; Glombitza, Clemens; Jørgensen, Bo Barker; Morono, Yuki; et al. (Frontiers in Microbiology, 2019)
Serpentinitic systems are potential habitats for microbial life due to frequently high concentrations of microbial energy substrates, such as hydrogen (H2), methane (CH4), and short-chain organic acids (SCOAs). Yet, many serpentinitic systems are also physiologically challenging environments due to highly alkaline conditions (pH>10) and elevated temperatures (>80C). To elucidate the possibility of microbial life in deep serpentinitic crustal environments, International Ocean Discovery Program (IODP) Expedition 366 drilled into the Yinazao, Fantangisña and Asùt Tesoru serpentinite mud volcanoes on the Mariana Forearc. These mud volcanoes differ in temperature (80, 150, 250C, respectively) of the underlying subducting slab, and in the porewater pH (11.0, 11.2, 12.5, respectively) of the serpentinite mud. Increases in formate and acetate concentrations across the three mud volcanoes, which are positively correlated with temperature in the subducting slab and coincide with strong increases in H2 concentrations, indicate a serpentinization-related origin. Thermodynamic calculations suggest that formate is produced by equilibrium reactions with dissolved inorganic carbon (DIC) + H2, and that equilibration continues during fluid ascent at temperatures below 80C. By contrast, the mechanism(s) of acetate production are not clear. Besides formate, acetate, and H2 data, we present concentrations of other SCOAs, methane, carbon monoxide, and sulfate, δ13C-data on bulk carbon pools, and microbial cell counts. Even though calculations indicate a wide range of microbial catabolic reactions to be thermodynamically favorable, concentration profiles of potential energy substrates and very low cell numbers suggest that microbial life is scarce or absent. We discuss the potential roles of temperature, pH, pressure, and dispersal in limiting the occurrence of microbial life in deep serpentinitic environments.